2023
DOI: 10.1002/agr.21836
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rural households' digital ability on their production efficiency in China

Abstract: Rural digitalization has become a key part of modernization in China. However, this rural digitalization follows a top‐down approach, from government guidance to private construction. Rural households' digital abilities have not received sufficient attention. This study explores rural households' digital abilities and their impact on production efficiency. One thousand eight hundred and seventy households are grouped into digital households (who have access to both digital and traditional channels) and traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Having multiple sources of income and engaging in different types of work can contribute to higher earnings and overall financial well-being for rural households. When comparing households with the same types of work, it is observed that the high-ability group tends to have higher incomes than the low-ability group, which is consistent with an empirical study [29]. This observation highlights the role of digital ability in promoting the income of rural households.…”
Section: Relationship Between Digital Ability Livelihood Diversificat...supporting
confidence: 85%
See 2 more Smart Citations
“…Having multiple sources of income and engaging in different types of work can contribute to higher earnings and overall financial well-being for rural households. When comparing households with the same types of work, it is observed that the high-ability group tends to have higher incomes than the low-ability group, which is consistent with an empirical study [29]. This observation highlights the role of digital ability in promoting the income of rural households.…”
Section: Relationship Between Digital Ability Livelihood Diversificat...supporting
confidence: 85%
“…This method is used to determine latent traits that are difficult to directly measure, such as cognitive abilities, personality traits, and attitudes. In agricultural economics, IRT is used to measure the information acquisition ability [28] or digital ability [25,29] of rural households. In the IRT strategy, respondents are asked to answer a set of binary questions of varying difficulty and discrimination, and their probability of success on this set of questions is positively correlated with their ability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation